Comparison of methods for constructing joint confidence bands for impulse response functions - Helmut Lütkepohl; Anna Staszewska-Bystrova; Peter Winker (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
In vector autoregressive analysis confidence intervals for individual impulse responses are typically reported to indicate the sampling uncertainty in the estimation results. A range of methods are reviewed and a new proposal is made for constructing joint confidence bands, given a prespecified coverage level, for the impulse responses at all horizons considered simultaneously. The methods are compared in a simulation experiment and recommendations for empirical work are provided.
Keywords: C32; 330; Vector autoregressive process; impulse responses; bootstrap; confidence band